Measurement of antibodies reacting with capsular antigens of Haemophilus influenzae - Turk, D. C. (1964)
A simple haemagglutination procedure is described which measures antibodies that react with capsular antigens of Haemophilus influenzae. Abnormally high antibody titres of appropriate type-specificity are common in the blood of human subjects who are known to have carried capsulate strains of H. influenzae. It is not yet clear whether all such antibodies are due to such carriage.